Quantitative Determination of Flavanone Content in Teki Grass Tuber (Cyperus rotundus L) using Ultraviolet-Visible Spectrophotometry - Fitriyati, Laeli; Nurani, Laela Hayu; Utami, Dwi; Widyaningsih, Wahyu (Journal of Food and Pharmaceutical Sciences, 2025)
Teki grass (Cyperus rotundus L.) tubers are medicinal plants that have been widely utilized for their anti-inflammatory, antioxidant, antibacterial, and anticancer properties. These pharmacological activities are attributed to the presence of polyphenolic compounds, particularly flavanones. This study aims to determine the flavanone content in teki grass tubers using UV-Vis spectrophotometry. The research was conducted as a laboratory-based experimental study, involving several steps: sample preparation, simplisia processing, extraction, and quantitative analysis of flavanone content by comparison with a flavanone standard. The UV-Vis spectrophotometric analysis revealed the presence of flavanones in the extract of teki grass tubers. Quantitative results showed that the flavanone concentration in the extract was 128.29 µg/mL. These findings confirm that teki grass tubers are a potential natural source of flavanones, supporting their traditional herbal medicine use.